Purification and characterization of a GH43 β-xylosidase from Enterobacter sp. identified and cloned from forest soil bacteria - Campos, Eleonora (2014)
The use of lignocellulosic biomass for second generation biofuels requires optimization of enzymatic breakdown of plant cell walls. In this work, cellulolytic bacteria were isolated from a native and two cultivated forest soil samples. Amplification of glycosyl hydrolases was attempted by using a low stringency-degenerate primer PCR strategy, using total soil DNA and bulk DNA pooled from positive colonies as template. A set of primers was designed based on Acidothermus cellulolyticus genome, by search of conserved domains of glycosyl hydrolases (GH) families of interest. Using this approach, a fragment containing an open reading frame (ORF) with 98% identity to a putative GH43 beta-xylosidase coding gene from Enterobacter cloacae was amplified and cloned. The full protein was expressed in Escherichia coli as N-terminal or C-terminal His-tagged fusions and purified under native conditions. Only N-terminal fusion protein, His-Xyl43, presented beta-xylosidase activity. On pNPX, optimal activity was achieved at pH 6 and 40 °C and Km and Kcat values were 2.92 mM and 1.32 seg−1, respectively. Activity was also demonstrated on xylobiose (X2), with Km 17.8 mM and Kcat 380 s−1. These results demonstrated that Xyl43 is a functional beta-xylosidase and it is the first evidence of this activity for Enterobacter sp.